PENGARUH IKLIM ORGANISASI TERHADAP INTENSI TURNOVER PADA KARYAWAN PT. GITA RIAU MAKMUR (HINO) PEKANBARU DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI - ", Nurjannah; ", Kasmiruddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to find out: 1) The influence of organizational climate on turnover intention of PT. Gita Riau Makmur (HINO) Pekanbaru, 2) Effect of organizational climate on Job Satisfaction of employees of PT. Gita Riau Makmur (HINO) Pekanbaru, 3) Effect of Job Satisfaction on turnover intentions of employees of PT. Gita Riau Makmur (HINO) Pekanbaru, 4) Effect of organizational climate on turnover intentions of employees of PT. Gita Riau Makmur (HINO) Pekanbaru through job satisfaction as a mediating variable.This research is a study using a quantitative approach. The subject of this research is PT. Gita Riau Makmur (HINO) Pekanbaru with 118 employees. Data collection using questionnaires, and data analysis using SEM-PLS analysis with warpPLS 4.0 software.The results of this study indicate that: 1) organizational climate has a significant negative effect on turnover intentions of employees of PT. Gita Riau Makmur (HINO) Pekanbaru, 2) organizational climate has a significant positive effect on job satisfaction of employees of PT. Gita Riau Makmur (HINO) Pekanbaru, 3) Job satisfaction has a significant negative effect on turnover intention of PT. Gita Riau Makmur (HINO) Pekanbaru, 4) Job satisfaction mediates the influence of organizational climate on turnover intention of PT. Gita Riau Makmur (HINO) Pekanbaru.Keywords: Organizational Climate, Turnover Intention, and Job Satisfaction.